Wavelet-Based Analysis Method for Heart Rate Detection of ECG Signal Using LabVIEW - Kaya, Duygu; Turk, Mustafa; Kaya, Turgay (Ieee, 2017)
LabVIEW is a graphical programming language that uses a dataflow model instead of sequential lines of text code. LabVIEW allows multiple operations to work in parallel. So, designers spend less time than a text based programming language. Application areas such as signal processing, image processing and data analysis are available. In this paper, wavelet analysis is used for the elimination of undesired frequency noise. In the obtained noise-free signal, the accurate heart rate was determined with helping of the program developed in the LabVIEW environment. The performance of the system was tested with different wavelet types and satisfactory results were obtained.
40th International Convention on Information and Communication Technology, Electronics and Microelectronics (MIPRO) -- MAY 22-26, 2017 -- Opatija, CROATIA
Keywords: LabVIEW; wavelet analysis; bioelectrical signal; ECG; heart rate detection